Linkage and the basic part of Witt rings - Yucas, Joseph L. (Annales Mathematicae Silesianae, 1991)
The strength of two axioms placed on a quaternionic mapping is compared. The first is the linkage axiom (L), and the second is the structure of the basic part axiom (X). It is shown here that (L) is strictly stronger than (X).